Well-of-the-well (WOW) versus polyester mesh (PM): a comparison of single-embryo culture systems in bovines - Contreras-Benicio, Daniel; Castro-Valenzuela, Beatriz Elena; Grado-Ahuir, Juan Alberto; Burrola-Barraza, María Eduviges (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Mexico is innovating in the livestock industry through in vitro generation of bovine embryos with technologies such as well-of-the-well (WOW) and polyester mesh (PM) single-embryo culture systems. These techniques allow to maintain embryos in separate areas of a shared culture medium. Objective: To compare the quantity and quality of bovine embryos produced in WOW and PM culture systems versus the conventional (CG) culture system. Methods: In total, 345 embryos fertilized in vitro were evaluated for blastocyst yield in the three culture systems. To count blastocyst cell numbers, 69 embryos in each system were differentially stained for trophectoderm (TE), inner cell mass (ICM), and apoptotic cells. A qPCR gene expression analysis was performed for embryos in all three systems. Results: The WOW, PM and CG systems developed similar amount of blastocysts (41, 35 and 36%, respectively; p>0.05). Blastocysts in all three systems showed adequate amounts of ICM and apoptotic cells. Blastocysts in the PM system showed a greater number of TE cells [63.7 versus 58.6% in the CG system (p<0.05)]. Relative mRNA expression of the embryonic genes POUF5F1, GNAS and TP53 did not differ significantly among systems (p>0.05). The ATP5B expression was higher in WOW than in PM (p<0.05), but similar to CG (p>0.05). The TJP3 expression was higher in PM than in WOW and CG (p<0.05). Expression of ID2 and CLDN4 was higher in WOW than in PM and CG (p<0.05). The biplot graphic from Principal Component Analysis (PCA) revealed that CG was located near degenerated embryos, whereas PM was located near arrested embryos, larger ICM and TE, and TJP3 expression. The WOW was located toward blastocysts, morulae, and expression of CLDN4, ID2 and GNAS. Conclusion: Compared with CG, both the PM and WOW systems are good options for culturing single embryos in the bovine model. Moreover, the PCA results suggest that embryos developed in the WOW system have greater capacity for generating blastocysts with increased ability to form TE and ICM layers, which might improve implantation.